Setting Sights on Human Rights. How China Is Undermining International Human Rights and Responses from the Liberal World - Friðrik Sigurbjörn Friðriksson 1986- (2018)
The rise of China in the international sphere has in recent years occupied increasingly greater space in geopolitical debate. Musings on the effect that China is having on the liberal international order, which has remained nearly unaltered since the end of World War II, are highly conspicuous. The aim of this thesis is to analyze the visible impact of China on one of the principal components of this system, i.e. international human rights. The basic concepts of human rights studies, universalism on the one hand, and cultural relativism on the other hand, are employed in order to examine how Communist China has interpreted human rights in international discourse, in opposition to the general interpretation of the majority of liberal states and leading international organizations, such as the United Nations. Furthermore, the manner in which China has been exerting itself to change this system according to its interpretation of whether human rights are universal or relative and aligned with the whimsy of the reigning governments of sovereign states is looked into. Then, the extensive financial expansion China has been undertaking in the last decades is scrutinized, as well as how the increased influence of the country within other states could reduce the prominence of human rights in coming years. Lastly, Iceland is used as an example of a liberal state that adopts a certain vision of human rights in the international arena, its relationship with China is discussed, along with the possibility of opposing the watering down of ideas regarding universal human rights in the international sphere. Ris Kína á alþjóðasviðinu hefur á síðustu árum tekið ört meira rými í alþjóðapólitískri umræðu. Vangaeltur um þau áhrif sem Kína er að hafa á hið frjálslynda alþjóðakerfi, sem staðið hefur nánast óbreytt frá lokum seinna stríðs, eru þar mjög áberandi. Markmið þessarar ritgerðar er að greina þessi sýnilegu áhrif sem Kína er að hafa á einn lykilkima þessa kerfis, eða málefni mannréttindi í heiminum. Hér er grundvallar hugtökum ...